2009
DOI: 10.1159/000270385
|View full text |Cite
|
Sign up to set email alerts
|

Responses to Intradermal Injections of Substance P in Psoriasis Patients with Pruritus

Abstract: Background: Various mediators have been suggested for the pathogenesis of pruritus in psoriasis. Methods: To investigate cutaneous responses of substance P in pruritic lesional and nonlesional areas of psoriasis patients and in healthy controls, substance P, saline and histamine were injected intradermally. After each injection, pruritus, flare and wheal were recorded. Results: There was no statistical difference in the latency period, duration, area under the curve and maximum intensity of pruritus evoked by … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
23
0

Year Published

2011
2011
2020
2020

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 30 publications
(26 citation statements)
references
References 48 publications
2
23
0
Order By: Relevance
“…However, the underlying mechanisms by which these chemicals mediate itch are unclear. Substance P has been reported to produce itch in humans mainly by degranulating mast cells to release histamine (Hagermark et al, 1978; Amatya et al, 2010). A wheal and flare accompanied the itch evoked by intradermal injections of substance P in these studies.…”
Section: Discussionmentioning
confidence: 99%
“…However, the underlying mechanisms by which these chemicals mediate itch are unclear. Substance P has been reported to produce itch in humans mainly by degranulating mast cells to release histamine (Hagermark et al, 1978; Amatya et al, 2010). A wheal and flare accompanied the itch evoked by intradermal injections of substance P in these studies.…”
Section: Discussionmentioning
confidence: 99%
“…We considered 5 min to be the most appropriate time period, based on earlier studies (e.g. 8,11,19), and on the results of a pilot study in the present investigation, which showed fairly constant values for wheal, while flare increased slightly over time (0-15 min). The maximum perpendicular diameters for the flare were measured in mm and the surface calculated in mm^ (20), while, for the wheal the maximum diameter in mm was recorded.…”
Section: Recording Experimental Pruritusmentioning
confidence: 95%
“…Administration of SP elicits scratching in both mice and humans through activation of the NK1R [166, 167]. Intrathecal injection of SP also rescues the loss of histamine-induced scratching in African naked mole rats [168].…”
Section: The Molecular Basis Of Pain and Itchmentioning
confidence: 99%